The Partnership for Rural Improvement: An Approach to Inter-Institutional Outreach - Robert H. McDaniel; Ralph A. Loomis (Educational Considerations, 1986)
Rural educators point to the need for increased inter-institutional collaboration - partly in response to scarce resources but also in response to the complex problems faced in many rural areas. This article examines some of the experience gleaned from ten years' work in interinstitutional collaboration directed by the Partnership for Rural Improvement.